Insights on the structure–function relationship of human multidrug resistance protein 7 (MRP7/ABCC10) from molecular dynamics simulations and docking studies. Issue 2 (25th March 2021) - Wang, Jing‐Quan; Cui, Qingbin; Lei, Zi‐Ning; Teng, Qiu‐Xu; Ji, Ning; Lin, Lusheng; Liu, Zhijun; Chen, Zhe‐Sheng
Abstract: ATP‐binding cassette (ABC) transporters superfamily mediates multidrug resistance in cancer by extruding structurally distinct chemotherapeutic agents, causing failure in chemotherapy. Among the 49 ABC transporters, multidrug resistance protein 7 (MRP7 or ABCC10) is relatively new and has been identified as the efflux pump of multiple anticancer agents including Vinca alkaloids and taxanes. Herein, we construct and validate a homology model for human MRP7 based on the cryo‐EM structures of MRP1. Structure–function relationship of MRP7 was obtained from molecular dynamics simulations and docking studies and was in accordance with previous studies of ABC transporters. The motion patterns correlated with efflux mechanism were discussed. Additionally, predicted substrate‐ and modulator‐binding sites of MRP7 were described for the first time, which provided rational insights in understanding the drug binding and functional regulation in MRP7. Our findings will benefit the high‐throughput virtual screening and development of MRP7 modulators in the future. Abstract : Homology modeling of MRP7 and predicted binding pocket characterization via docking analysis.